Volunteering – An Efficient Collaborative Practice for the Local Communities Sustainability. Empirical Study - Predețeanu-Dragne, Daniela; Popescu, Dan; Nicolae, Valentina (European Journal of Sustainable Development, 2019)
The scientific research we have conducted concerns volunteering as a collaborative practice and as a basis for the sustainable development of local communities. Identifying the suitable practices capable of transforming a group of individuals into a prosperous and sustainable collaborative community has became our priority concern. Therefore, the main objective of the study was outlined as a response to the question: “which are the tangible and intangible effects of the acts and facts of the collaboration identified in the communities where the participants in the study came from?”. The answer was prefigured as the outcome of an exploratory analysis that also revealed to us the motivation, satisfaction and results obtained by the participants in the survey, as a consequence of their personal experience in relation to their community. The quantitative analysis of collected data was performed in IBM SPSS software and the qualitative analysis with the Atlas Ti application. Despite the poverty of information sources in the field, our exploratory research has succeeded in highlighting the role of volunteering as a factor of sustainable social cohesion and practice in local communities. And this is at least one of our reasons useful to continue our theoretical and applied researches related to the emergence and sustainable development of collaborative communities. Keywords: exploratory analysis; collaborative community; sustainability; social economy enterprise; social innovation